The Grass Is Not Always Greener on the Other Side: Seasonal Reversal of Vegetation Greenness in Aspect‐Driven Semiarid Ecosystems - Kumari, Nikul; Saco, Patricia M.; Rodriguez, Jose F.; Johnstone, Samuel A.; Srivastava, Ankur; Chun, Kwok P.; Yetemen, Omer (American Geophysical Union (AGU), 2020)
AbstractOur current understanding of semiarid ecosystems is that they tend to display higher vegetation greenness on polar‐facing slopes (PFS) than on equatorial‐facing slopes (EFS). However, recent studies have argued that higher vegetation greenness can occur on EFS during part of the year. To assess whether this seasonal reversal of aspect‐driven vegetation is a common occurrence, we conducted a global‐scale analysis of vegetation greenness on a monthly time scale over an 18‐year period (2000–2017). We examined the influence of climate seasonality on the normalized difference vegetation index (NDVI) values of PFS and EFS at 60 different catchments with aspect‐controlled vegetation located across all continents except Antarctica. Our results show that an overwhelming majority of sites (70%) display seasonal reversal, associated with transitions from water‐limited to energy‐limited conditions during wet winters. These findings highlight the need to consider seasonal variations of aspect‐driven vegetation patterns in ecohydrology, geomorphology, and Earth system models.
Keywords: ecosystem; semiarid; remote sensing; NDVI; vegetatio greenness; hillslope aspect